Implementation of a medication reconciliation process in an ambulatory internal medicine clinic - Nassaralla, Claudia L (BMJ Group, 2007)
OBJECTIVE: To evaluate the causes of medication list inaccuracy, implement intervention to enhance overall accuracy of medication lists and measure the sustainability of the intervention. METHODS: A prospective study of patients seen in an academic, ambulatory primary care internal medicine clinic. Before the intervention, baseline data were analysed, assessing completeness of medication documentation in the electronic medical record. The intervention consisted of standardising the entire visit process from scheduling of the appointment to signing of the final clinical note by the physician. Each healthcare team member was instructed in her role to enhance accuracy of the documented medication list. Immediately after the intervention, a second data collection was undertaken to assess the effectiveness of the intervention on the accuracy of individual medications and medication lists. Finally, a year later, a third data collection was undertaken to assess the sustainability of the intervention. RESULTS: Completeness of individual medications improved from 9.7% to 70.7% (p<0.001). However, completeness of the entire medication lists improved only from 7.7% to 18.5%. The incomplete documentation of medication lists was mostly due to lack of route (85.8%) and frequency (22.3%) for individual medications within a medication list. Also, documentation of over‐the‐counter and “as needed” medications was often incomplete. The incorrectness in a medication list was mostly due to misreporting of medications by patients or failure of clinicians to update the medication list when changes were made. CONCLUSION: To improve the accuracy of medication lists, active participation of all members of the healthcare team and the patient is needed.